2021
DOI: 10.3390/healthcare9050609
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Advice and Counselling by Healthcare Providers: A Scoping Review

Abstract: Background: Despite scientific evidence on prenatal physical activity and exercise, synthesized evidence is lacking on the provision of prenatal physical activity and exercise advice and counselling by prenatal healthcare providers. The scoping review seeks to fill this gap by synthesizing available literature on the provision of prenatal physical activity and exercise advice and counselling by prenatal healthcare providers to women during antenatal visits. Methods: The Preferred Reporting Items for Systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 57 publications
(136 reference statements)
0
14
0
2
Order By: Relevance
“…International [ 9 , 10 ] and national [ 11 ] health organisations recommend that health professionals promote physical activity within their routine practice, and health professionals themselves strongly believe that they should be doing this [ 12 , 13 ]. However, healthcare systems have failed to implement and scale-up physical activity promotion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…International [ 9 , 10 ] and national [ 11 ] health organisations recommend that health professionals promote physical activity within their routine practice, and health professionals themselves strongly believe that they should be doing this [ 12 , 13 ]. However, healthcare systems have failed to implement and scale-up physical activity promotion.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys of health professionals [ 12 15 ], audits of medical records [ 16 ] and surveys of patients [ 16 19 ] from around the world confirm that physical activity promotion, including counselling, is not routinely delivered in healthcare. Health professionals report that common barriers to delivery of this intervention include insufficient reimbursement, resources, time, knowledge, skills, training, protocols and organisational routines that do not support implementation [ 12 , 13 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study investigating leisure-time PA in women with gestational diabetes showed that more than one fourth of all women reported an absence of encouragement for leisure-time PA from healthcare providers ( 25 ). The lack of professional support and regular advice might be attributed to limited time, knowledge and resources available on this topic among healthcare providers ( 20 , 25 ). Moreover, even though healthcare providers meet with pregnant women on a regular basis, they cannot offer daily or additional support when needed.…”
Section: Discussionmentioning
confidence: 99%
“…Social support can be categorized into four groups of support: (1) emotional support; (2) informational or cognitive support; (3) instrumental support (i.e., assistance received in terms of tangible goods, services or aid) and (4) appraisal support (i.e., information useful for self-evaluation) ( 18 , 19 ). Professional advice is perceived as important in the promotion of a healthy lifestyle during pregnancy ( 20 ) and might be important for informational support. Family and friends on the other hand seem to be a constant source of information and advice throughout pregnancy ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wenn Frauen über die Bewegungsempfehlungen informiert sind, behalten sie ihr Bewegungsniveau bei oder steigern es sogar [8,25]. Gesundheitsfachkräfte wie Hebammen, Gynäkolog*innen, Allgemeinmediziner*innen, Expert*innen in Sport und Bewegungswissenschaften, Physiotherapeut*innen und Ernährungsberater*innen sind gefordert, Frauen im Hin-blick auf ihre Selbstwirksamkeit ("Empowerment") im Bereich kA und Sport zu unterstützen [20,25]. Gesundheitsfachkräfte, die Schwangere betreuen, sollten deshalb mit den internationalen Empfehlungen für Bewegung vertraut sein.…”
Section: Bedeutung Körperlicher Aktivität In Der Schwangerschaftunclassified